Economic challenges facing Singapore in the 21st century. - Lim, Khai Dee. (2008)
The Singapore economy has grown tremendously. Despite the various problems and challenges we faced along the way, we managed to come up with appropriate responses and solutions. Globalization and the new knowledge economy will take centre-stage in the 21st century. Hence, we have identified the economic challenges ahead of us.